Method for Analysis and Classification of Pavement Based on Quality - Asatryan , Davit. G.; Hakobyan, Gurgen H. (Mathematical Problems of Computer Science, 2021)
The main objective of automated systems for pavement quality control is the detection of cracks and other surface defects, as well as the analysis of their corresponding parameters. On pavement areas the quality assessment is performed based on video surveys, followed by image processing with the corresponding mathematical methods. In this paper, a method for classification of video survey frames from pavement with and without cracks is proposed. Each frame is processed with previously proposed methods of binarization and segmentation. As a result, two classes are formed for classification experiments based on the proposed procedures. The method of comparison with etalons is used, with application of proximity measure based on structural properties of images. On experimental data it is shown, that the proposed method of pavement classification gives acceptable results (the average of classification inaccuracy is about 26%).